2020
DOI: 10.3390/s20051277
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Algorithm for the Detection of Preimpact Fall for Wearable Airbags

Abstract: Fall-related injury is a common cause of mortality among the elderly. Hip fractures are especially dangerous and can even be fatal. In this study, a threshold-based preimpact fall detection algorithm was developed for wearable airbags that minimize the impact of falls on the user’s body. Acceleration sum vector magnitude (SVM), angular velocity SVM, and vertical angle, calculated using inertial data captured from an inertial measurement unit were used to develop the algorithm. To calculate the vertical angle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…While some studies extracted handcrafted features and constructed fixed-threshold algorithms for real-world use, Jung et al [ 17 ] obtained 100% sensitivity, 97.54% specificity, and 98.33% accuracy on their private dataset, and achieved relatively high performance in comparison to some similar studies on the SisFall dataset. However, as shown in Table 1 , when evaluating Jung’s algorithm with our experimental data, 87.16% accuracy and 77.36% specificity were achieved, due to the diversity of individuals, behaviors, and environments.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies extracted handcrafted features and constructed fixed-threshold algorithms for real-world use, Jung et al [ 17 ] obtained 100% sensitivity, 97.54% specificity, and 98.33% accuracy on their private dataset, and achieved relatively high performance in comparison to some similar studies on the SisFall dataset. However, as shown in Table 1 , when evaluating Jung’s algorithm with our experimental data, 87.16% accuracy and 77.36% specificity were achieved, due to the diversity of individuals, behaviors, and environments.…”
Section: Discussionmentioning
confidence: 99%
“…The VA was calculated using a complementary filter with a PI controller [ 34 ] to minimize integration errors and the effect of external impacts. Figure 5 shows the flowchart of a complementary filter with the PI controller.…”
Section: Methodsmentioning
confidence: 99%
“…Their algorithm achieved 100% sensitivity, three false alarms (the number of non-falls detected as falls), and a lead time of over 70 ms. Nyan et al [ 32 ] also developed a threshold-based pre-impact fall detection algorithm using angles calculated from the torso and thigh (with two IMUs), as well as the correlation coefficients of the torso and thigh angles. The algorithm achieved 100% specificity, 95.2% specificity, and a lead time of 700 ms. Sabatini et al [ 33 ] estimated the vertical velocity and height change using an IMU with a barometric altimeter to detect fall and achieved 80% sensitivity, 100% specificity, and an average lead time of 157 ms. Jung et al [ 34 ] performed experiments on 30 healthy young males and obtained inertial data from the back waist. A fall detection algorithm was developed using acceleration RMS, angular velocity RMS, and vertical angle (VA).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have begun to shift their focus from post-fall detection to pre-impact fall detection and shed some light on this topic. Jung et al (2020) developed a threshold-based algorithm, which combined multiple thresholds (magnitude of acceleration, magnitude of angular velocity, and vertical angle) based on inertial sensors for pre-impact fall detection and achieved 100% sensitivity and 97.54% specificity with an average lead time of 280 ms. This algorithm was developed based on their own simulated dataset with six types of falls and 14 types of activities of daily living (ADLs) by 30 young subjects.…”
Section: Introductionmentioning
confidence: 99%
“…This poses a challenge to fairly evaluate the performance of different algorithms on a common basis and their generalizability to different datasets. A few preliminary studies showed that algorithms based on a specific database with good performance had poor external validity on other databases (Sabatini et al, 2015;Jung et al, 2020). For instance, when Jung et al (2020) applied their thresholds to the SisFall dataset (Sucerquia et al, 2017), both sensitivity and specificity dropped considerably by 4 and 7%, respectively.…”
Section: Introductionmentioning
confidence: 99%